Technologies for increasing students’ institutional trust in authorities during globalisation of the network information space - V. A. Yudina; V. V. Bondarenko; I. A. Yurasov (Вестник университета)
In the conditions of geopolitical instability, globalisation of information space, cultural and digital transformations, it is necessary to pay special attention to the problems of preservation of identity and formation of students’ state-oriented active citizenship, also on the basis of using socio-communicative technologies for managing institutional trust in the authorities. The subject of the study – elements of communicative policy of government officials, public organisations, mass media, aimed at student youth. The purpose of the study is to develop a set of modern technologies to increase the level of students’ institutional trust in the authorities. The research methodology is based on theoretical and methodological provisions of sociology, social psychology, political science to define the phenomena of institutional and social trust as well as the concept of a single information space. As a result of the empirical study, the authors have determined the level of trust in regional and federal authorities, individual socio-economic and political institutions put by students from higher and secondary professional educational organisations; the authors have also identified the causes of low awareness and involvement of student youth in public processes of regional development, and low participation in the activities of specialised all-Russian and regional youth organisations. The technologies for improving the effectiveness of interaction between the authorities and students, as well as in the network information space, are proposed as recommendations.